Implementation of View Controller Model Architecture in Population Administration Service System - dina mariyanti; iwan santosa; eza rahmanita (International Journal of Science, Engineering, and Information Technology, 2017)
Population administration services at the Kamal sub-district office are currently still using manual methods. This causes the administrative service process in the Kamal subdistrict office to not run efficiently. Therefore, an application for a web-based population administration service system is needed that is built with the Model View Controller architecture using a Codeigniter framework. Using the MVC architecture there are several benefits including software development that is easy to repair. By using the MVC architecture can bring changes that facilitate the demographic service process in the district Kamal, and can also can shorten the processing time of the service so as to reduce the buildup of queues and also facilitate the admin in the district office Kamal in the data search process of residents residing in the district Kamal. The result of the research show that MVC implementation on population administration service system applications can be easily used and developed again.